Assessment of primary ciliary dyskinesia predictive tools. Issue 6 (10th December 2020) - Palmas, Kaitlyn; Shanthikumar, Shivanthan; Robinson, Philip
Primary ciliary dyskinesia (PCD) is an important cause of suppurative airway disease and other comorbidities [1]. Due to nonspecific signs and symptoms, the diagnosis of PCD is challenging, requiring specific expertise [2, 3]. PCD testing should be conducted at specialised PCD centres; however, in many places testing is not readily available. Predictive tools based on clinical presentation would help clinicians triage referral for specialised testing. Two such predictive tools have been developed: the PICADAR score [4] and North American Criteria Defined Clinical Features (NA-CDCF) [5]. There has been little validation of these tools outside the settings where they were developed. The original PICADAR publication contained a constructed validation cohort of 187 patients, half of whom had PCD. A novel real-world validation of two tools (PICADAR and NA-CDCF) that use routinely collected clinical data and help triage the need for primary ciliary dyskinesia diagnostic testing is performed, showing both tools perform well with equivalent performance https://bit.ly/2YgzxlY